Effects of Minimum Wage Increases on Employment in Lithuania - Šuminas, Mykolas (Ekonomika, 2015)
From the advent of minimum wage it was subject to controversy: economists did not agree on its effects on the state of the economy, the welfare of both firms and workers. Empirical academic literature usually investigates employment reaction to the minimum wage fluctuations. Regrettably, such papers do not exist for Lithuania, so the literature of similar scope and topic of the US and UK (along with several other countries) is explored in this paper. The effect of the Lithuanian real minimum wage on aggregate employment is estimated by using time series models. Dependant on the specification, the real minimum wage elasticity is estimated to be –0.03–0.03 yet statically insignificant in all of the models. The result is in line with the reviewed literature; more precisely most of papers published in mid-1990s and beyond do not register any significant minimum wage effects on employment. The phenomenon is attributed to the fact that firms can exploit other channels (raising prices, hiring more productive employees, etc.) to make adjustments to new, higher wages. The paper does not explore what channels were used by the firms; however, a possible channel of productivity is investigated. Moreover, the temperate minimum wage policy is one of the factors that could have led to the insignificance of minimum wage to employment conclusion: the nominal minimum wage was only raised during the period of economic growth, and during economic downturns and recoveries it was frozen. The claim is further supported by the share of minimum wage earners in respect to total employed and the minimum wage to average wage ratio: the variables were relatively constant from 2005 onwards.